2010
DOI: 10.1080/02757541003705492
|View full text |Cite
|
Sign up to set email alerts
|

Meiofauna of the Adriatic Sea: present knowledge and future perspectives

Abstract: Owing to technical problems and difficult taxonomic identification, meiofauna have been generally less studied than macrofauna. However, the role of meiofauna in marine ecosystem functioning, and their effective and rapid response to anthropogenic alterations and climatic changes have recently been acknowledged, leading to increasing scientific and applied interest. At present, systematic and biogeographic knowledge of the meiofauna of the Adriatic Sea is extremely heterogeneous, because most of the data are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…When comparing similar sampling periods (i.e., June), abundances were even more alike, suggesting that sediment contamination, especially at St. 2 and 3, did not seem to severely affect total meiofaunal numbers. The community, dominated by nematodes and copepods as in most coastal areas of the Adriatic Sea (Balsamo et al, 2010), reflected the composition already reported for the Gulf of Trieste (Cibic et al, 2009). Compared to the stations inside the port area, the highest number of meiofaunal groups (n = 10) was reported at St. C1, suggesting the presence of a more structured community at the reference station.…”
Section: Discussion Benthic Trophic Web In the Port Areamentioning
confidence: 65%
See 1 more Smart Citation
“…When comparing similar sampling periods (i.e., June), abundances were even more alike, suggesting that sediment contamination, especially at St. 2 and 3, did not seem to severely affect total meiofaunal numbers. The community, dominated by nematodes and copepods as in most coastal areas of the Adriatic Sea (Balsamo et al, 2010), reflected the composition already reported for the Gulf of Trieste (Cibic et al, 2009). Compared to the stations inside the port area, the highest number of meiofaunal groups (n = 10) was reported at St. C1, suggesting the presence of a more structured community at the reference station.…”
Section: Discussion Benthic Trophic Web In the Port Areamentioning
confidence: 65%
“…Indeed, among the physical variables, grain size is considered one of the most important factors influencing the colonization of sediments by benthic organisms at different trophic levels, from microphytobenthos (Round et al, 1992) to meiofauna (Balsamo et al, 2010) and macrofauna (Solis-Weiss et al, 2004). Within the port area, St. 6 differed from the other stations primarily by its reduced depth (8.5 m) and a higher percentage of sand (about 40%) that favored high macrofaunal abundances.…”
Section: Discussion Benthic Trophic Web In the Port Areamentioning
confidence: 99%
“…Moreover, well-documented habitat destruction, over-fishing, water pollution and eutrophication, species introduction, and climatic changes make the Mediterranean a key area for studying the influence of natural and anthropogenic changes on biodiversity . In the Adriatic Sea, which is a closed basin, these changes may even be enhanced, leading to its greater vulnerability (Balsamo et al 2010). Protection and management programmes are required to conserve the coastal areas and their communities, with a special focus on the most sensitive and vulnerable environments.…”
Section: Introductionmentioning
confidence: 99%
“…Free-living nematodes are the most diverse and numerically dominant metazoans in aquatic ecosystems (Balsamo et al 2010, Appeltans et al 2012). This phylum is particularly important for studying TEs due to its ability to persist during environmental perturbations which may reduce or eliminate macrofauna (Hendelberg and Jensen 1993).…”
Section: Introductionmentioning
confidence: 99%